“Responsible” or “Strange?” Differences in Face Mask Attitudes and Use Between Chinese and Non-East Asian Canadians During COVID-19’s First Wave - Zhang, Ying Shan Doris; Noels, Kimberly A.; Young-Leslie, Heather; Lou, Nigel Mantou (Frontiers in Psychology, 2022)
Early in the COVID-19 pandemic, journalists and scholars noted differences between Asians and North Americans in their support for public mask use. These differences were primarily assumed to be due d to variations in ethnocultural norms and practices. To better ascertain people’s motives for wearing masks and potential cultural differences in these rationales, this comparative, mixed-methods research examines Chinese and non-East Asian Canadians’ mask use attitudes utilizing online group interviews (Study 1) and a nation-wide survey (Study 2) Study 1, conducted in the early stages of the pandemic, captured an ambivalent, yet evolving attitude toward public mask use among the non-East Asian Canadians, which differed from their Chinese counterparts who more uniformly perceived mask use favorably. Study 2, conducted 2 months later, suggests that both groups primarily wore masks for disease protection- and prevention-related reasons. However, age and education appeared to influence the mask wearing frequency of the non-East Asian Canadians, for whom public mask use was less prevalent and normative. The attitudinal differences in public mask use call for targeted strategies to support mask wearing for different ethnocultural groups, which may be achieved partially through enhancing interethnic understanding on the diversified use of and opinions about masks. The findings suggest that favourable social norms, along with evidence-based information campaigns involving personal appeals may encourage greater mask use by the non-East Asian population.